O cuidado na prática do psicólogo no Centro de Referência de Assistência Social (CRAS) - Oliveira, Patrícia Araújo de (2019)
The dissertation will discuss the conduct of psychologists in public policies from the perspective of this researcher, who is a public employee working at the Social Assistance Referral Center (CRAS), the basic protection equipment of the Social Assistance System (SUAS). Using references from the history of SUAS and the Health System (SUS), as well as accumulated experiences and experiences, an action is proposed that has Cuidado (“Care”) as a basis. Using Socio-Historical psychology, especially Vygotsky (1896-1934) as a reference, a model will be proposed that uses the Zone of Proximal Development as a method for achieving integral care. Two interviews with professionals of the area were carried out. The researcher's testimony was also used as basis for the analysis. A way of acting that respects the individual stories, the projects of life and happiness was pursued